Transformasi Sosial Petani Kentang di Dataran Tinggi Dieng - Turasih Turasih (UIN Siber Syekh Nurjati Cirebon, 2019)
Potato commodities present after the era of corn and tobacco in Dieng Plateau in the early stages contribute significantly to the economic aspects of farmers. High selling price and short planting season cause farmers to do the potato farming activities intensively. The inclusion of potato commodities led to the modernization of agriculture and created the social stratification gap of farmer communities in terms of production mode mastery. Population growth then complicate the issue. Agricultural activities have penetrated the environmental destruction on the basis of agricultural and residential needs. The impact is reduced environmental support and also the income of farmers. The modern agricultural system in Dieng Plateau creates a new economic structure relating to the capitalist market and contributes to ecological damage. The problems that occur in Dieng Plateau attract the attention of various parties to perform the recovery through the process of 'empowerment'. Unfortunately, the empowerment process is still technically biased and makes the poor as well as the farmer as an object.